2013
DOI: 10.2319/010213-5.1
|View full text |Cite
|
Sign up to set email alerts
|

Unilaterally impacted maxillary central incisor and canine with ipsilateral transposed canine-lateral incisor

Abstract: Concurrent impaction and transposition of maxillary anterior teeth is uncommon and poses a challenge for dentists. Early diagnosis and management of eruption disturbances benefits esthetic and functional outcomes. This article describes the treatment of a teenager who had impactions of the left maxillary central incisor and canine as well as ipsilateral canine-lateral incisor transposition. Treatment alternatives and effective orthodontic techniques are delineated. To optimize the treatment results, the impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
0
8
1
1
Order By: Relevance
“…The differences found in this study for the number of male and female patients (ratio 1:1) and the frequency of unilateral and bilateral impactions (60% and 40% respectively) from what’s described in literature ( 6 , 9 ), might be explained by the reduced sample size.…”
Section: Discussioncontrasting
confidence: 76%
“…The differences found in this study for the number of male and female patients (ratio 1:1) and the frequency of unilateral and bilateral impactions (60% and 40% respectively) from what’s described in literature ( 6 , 9 ), might be explained by the reduced sample size.…”
Section: Discussioncontrasting
confidence: 76%
“…According to these findings, Chaushu and colleagues suggested that early treatment for central incisor impaction can be effective to prevent a canine impaction on the same side (18). Although the main cause of dental transpositions is still unknown, etiologic causes such as trauma, genetics, and displacement of developing dental bud, mechanical interruptions, early loss of primary teeth and over retention of primary dentition (6) and dental transposition of lateral and canine on the same side can lead to greater challenges.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, only one of the central incisors has eruption problem, but in more severe cases, both central incisors have the problem (9). Frequency of central impactions is reported to be 0.06% to 0.2% (6).…”
mentioning
confidence: 99%
“…Elastik intermaksila yang dipasang dari gigi molar pertama rahang atas ke kaninus bawah dapat digunakan untuk koreksi gigitan terbalik anterior. 7 Efek yang diharapkan adalah dapat memberikan labial root torque pada archwire dan terjadi distalisasi gigi anterior rahang bawah dan protraksi gigi anterior rahang atas. Pada saat berbicara pasien dapat membuka mulut sebesar 10 mm, keadaan ini akan memberikan gaya yang bervariasi bergantung pada angulasi elastik intermaksila dan efeknya pun akan bervariasi terhadap lengkung rahang atas dan rahang bawah.…”
Section: Kata Kunci: Gigitan Terbalik Anterior Posterior Rapid Maxilunclassified